2023
DOI: 10.3390/plants12010194
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive Biochemical Response to Water Stress in Interspecific Eggplant Hybrids

Abstract: In a climate change scenario, crop tolerance to drought must be urgently improved, as it represents an increasingly critical stress reducing agricultural yields worldwide. Although most crops are relatively sensitive to water stress, many of their wild relatives are more tolerant and may be used to improve drought tolerance in our crops. In this study, the response to drought of eggplant (Solanum melongena), its close wild relatives S. insanum and S. incanum and their interspecific hybrids with S. melongena wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 93 publications
(104 reference statements)
2
2
0
Order By: Relevance
“…In a study, eggplant, its close wild relatives S. insanum and S. incanum and their interspecific hybrids with S. melongena were subjected to drought for 18 days. Their results which were support our results, showed that the hybrid between S. melongena and S. incanum displayed a better response than the other hybrids and even its parents (González-Orenga et al, 2023). On the 25 th day of the treatment 4 of 12 each 50 F4 plants showing "slow growth" (Scale = 1) were selected as "tolerant to drought" by using 0-5 scale.…”
Section: Resultssupporting
confidence: 88%
“…In a study, eggplant, its close wild relatives S. insanum and S. incanum and their interspecific hybrids with S. melongena were subjected to drought for 18 days. Their results which were support our results, showed that the hybrid between S. melongena and S. incanum displayed a better response than the other hybrids and even its parents (González-Orenga et al, 2023). On the 25 th day of the treatment 4 of 12 each 50 F4 plants showing "slow growth" (Scale = 1) were selected as "tolerant to drought" by using 0-5 scale.…”
Section: Resultssupporting
confidence: 88%
“…Prediction of polygenic traits, such as those tested in this trial, is usually a major challenge in hybrid generation [ 56 ]. These results are similar to those found in other studies that have evaluated F 1 eggplant hybrids under water stress, where the responses were diverse and complex due to the genetic distance of the parents [ 16 , 57 ], the generation of hybrids with parents presenting moderate genetic distances could be a better strategy, as it has been seen that they achieve better results in eggplant [ 58 ]. At the growth level, the hybrids did not stand out in any trait under water stress, but it was observed that two hybrids had lower H 2 O 2 content, which could indicate a lower level of oxidative stress [ 59 ], and one hybrid had lower proline content, which could indicate a lower level of stress [ 60 ].…”
Section: Discussionsupporting
confidence: 89%
“…The use of hybrid varieties has led to significant advances in agriculture, with the potential to increase production and resilience to biotic and abiotic stresses [ 15 ]. In eggplant, promising responses under water stress conditions have been identified through hybridization, with interspecific hybrids of S. melongena × S. incanum and S. melongena × S. insanum showing superior growth under limited water supply compared to their parents [ 16 ]. In addition, Multiparent Advanced Generation Intercrossing (MAGIC) populations are increasingly recognised as a powerful tool for plant breeding, facilitating the identification of genomic regions and the selection of recombinant lines with desired traits [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of straightforward growth metrics is often adequate for closely related genotypes, such as varieties or cultivars of one species or even species belonging to the same genus. Some examples include permanent wilting in cowpea [45], roots system size in barley [46], reduction of fresh shoots biomass accumulation in Juncus [47], foliar dehydration in Limonium [48], reduction of leaf area and leaf fresh weight in eggplants and its hybrids [49], and shoot and leaf dry weight in wild relatives of eggplant [50], amongst others. However, in addition to growth characteristics, physiological, biochemical, and more recently, omics approaches are also considered when screening a larger number of more distant genotypes for drought resistance [51][52][53][54][55][56][57] (amongst many others).…”
Section: Discussionmentioning
confidence: 99%